The effect of cetyltrimethylammonium bromide on size and morphology of ZnO and CuO - Anantha N. Subba Rao; Venkatesha T. Venkatarangaiah (Journal of Electrochemical Science and Engineering, 2014)
The nanoparticles (NP) ZnO and CuO were synthesized by electrochemical-thermal method. The influence ofcetyltrimethylammonium bromide (CTAB) on size and morphology of NP was evaluated. They were characterized by powder X-ray diffraction spectroscopy (XRD), scanning electron microscopy (SEM), UV-Visible absorption spectroscopy. The average crystallite size and the average grain size of NP decreased with CTAB concentration. The CTAB significantly affected the morphology of CuO and ZnO NP. The regular spindle shape of CuO transformed into irregular spherical shape and the homogeneity in the morphology of spherical ZnO NP was lost with increase in CTAB concentration. The effect of morphology and size of ZnO on its photocatalytic activity was evaluated by subjecting methylene blue (MB) dye to photocatalytic degradation under the irradiation of UV light. The color removal of MB dye during electrolysis was monitored by UV-Visible spectroscopy. The highest photocatalytic activity was noticed for ZnO 10 mM CTAB.